CTCF-mediated chromatin loops enclose inducible gene regulatory domains. (December 2016) - Oti, Martin; Falck, Jonas; Huynen, Martijn; Zhou, Huiqing
Abstract Background The CCTC-binding factor (CTCF) protein is involved in genome organization, including mediating three-dimensional chromatin interactions. Human patient lymphocytes with mutations in a single copy of the CTCF gene have reduced expression of enhancer-associated genes involved in response to stimuli. We hypothesize that CTCF interactions stabilize enhancer-promoter chromatin interaction domains, facilitating increased expression of genes in response to stimuli. Here we systematically investigate this model using computational analyses. Results We use CTCF ChIA-PET data from the ENCODE project to show that CTCF-associated chromatin loops have a tendency to enclose regions of enhancer-regulated stimulus responsive genes, insulating them from neighboring regions of constitutively expressed housekeeping genes. To facilitate cell type-specific CTCF loop identification, we develop an algorithm to predict CTCF loops from ChIP-seq data alone by exploiting the CTCF motif directionality in loop anchors. We apply this algorithm to a hundred ENCODE cell line datasets, confirming the universality of our observations as well as identifying a general distinction between primary and immortal cells in loop-enclosed gene content. Finally, we combine the existing evidence to propose a model for the formation of CTCF loops in which partner sites are brought together by chromatin template reeling through stationary RNA polymerases, consistent with the transcription factory hypothesis. Conclusions We provide computational evidence that CTCF-mediated chromatin interactions enclose domains of stimulus responsive enhancer-regulated genes, insulating them from nearby housekeeping genes.